Digital transformation in public-private collaborations : The success of humanitarian supply chain operations - Akhtar, Pervaiz; De Silva, Muthu; Khan, Zaheer; Tarba, Shlomo; Amankwah-Amoah, Joseph; Wood, Geoffrey (Elsevier, 2024)
Recent years have seen the extensive use of big data analytics, related technological infrastructure, and machine learning applications for digital transformation. The resource dependency related to data-driven applications elicits public-private collaborations (PPCs) between governments and private or non-government organizations (NGOs) for value creation. Such collaborations are effective for the success of humanitarian supply chain operations (HSCOs), particularly in the event of large-scale disasters. By building on resource dependence theory (RDT), our study explores the links between digital transformation, PPCs, and HSCO success. Using structural equation modeling on data collected from 224 key decision-makers and experts, we found that digital transformation mediates the relationship between private-NGO collaborations and HSCO success while host government support moderates it. Our study thus makes an original contribution to RDT and the emerging domains of contemporary digital and data-driven applications in HSCO. The implications and future research directions arising from this study are also discussed in this research paper.
Keywords: Digital transformation; Big data IT infrastructure; Big data analytics; Machine learning and statistics; Public-private collaborations; The success of humanitarian supply chain operations